2014
DOI: 10.3390/ijms151222042
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of the Flavoring Agent Zingerone and of both (R)- and (S)-Zingerols via Green Fungal Biocatalysis. Comparative Antifungal Activities between Enantiomers

Abstract: Zingerone (1) and both chiral forms of zingerol (2) were obtained from dehydrozingerone (3) by biotransformation with filamentous fungi. The bioconversion of 3 with A. fumigatus, G. candidum or R. oryzae allowed the production of 1 as the sole product at 8 h and in 81%–90% at 72 h. In turn, A. flavus, A. niger, C. echinulata, M. circinelloides and P. citrinum produced 1 at 8 h, but at 72 h alcohol 2 was obtained as the major product (74%–99%). Among them, A. niger and M. circinelloides led to the anti-Prelog z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Moreover, these compounds demonstrated in vitro cytotoxic activity against some cancer cell lines (HeLa, LS174, and A549) [22]. Svetaz et al (2014) have studied biotransformation and antifungal activity of DHZ and two of its derivatives on some filamentous fungi, including Aspergillus, Fusarium, Geoterichum, Cunninghamella, Mucor, Penicillium, Rhizopus, and Trichosporum [23]. In the present study, we showed that the growth and biofilm 2021 Vol.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, these compounds demonstrated in vitro cytotoxic activity against some cancer cell lines (HeLa, LS174, and A549) [22]. Svetaz et al (2014) have studied biotransformation and antifungal activity of DHZ and two of its derivatives on some filamentous fungi, including Aspergillus, Fusarium, Geoterichum, Cunninghamella, Mucor, Penicillium, Rhizopus, and Trichosporum [23]. In the present study, we showed that the growth and biofilm 2021 Vol.…”
Section: Discussionsupporting
confidence: 50%
“…[53] C). [24] [ 13 C NMR (101 MHz, CDCl 3 ) δ 146.4, 143.7, 133.9, 120.92, 114.2, 110.9, 67.6, 55.9, 41.1, 31.8, 23.7. [24] ½ � 20 D = À 14.06 (c 0.398, CHCl 3 ).…”
Section: Characterization Of Isolated and Synthesized Compoundsmentioning
confidence: 99%
“…[24] [ 13 C NMR (101 MHz, CDCl 3 ) δ 146.4, 143.7, 133.9, 120.92, 114.2, 110.9, 67.6, 55.9, 41.1, 31.8, 23.7. [24] ½ � 20 D = À 14.06 (c 0.398, CHCl 3 ). 1 H NMR (400 MHz, CDCl 3 ) δ 6.84 (d, J = 7.8 Hz, 1H), 6.71 (d, J = 9.4 Hz, 2H), 5.61 (s, 1H), 3.88 (s, 3H), 3.83 (dd, J = 12.1, 6.1 Hz, 1H), 2.74-2.57 (m, 2H), 1.80-1.72 (m, 2H), 1.24 (d, J = 6.1 Hz, 3H).…”
Section: Characterization Of Isolated and Synthesized Compoundsmentioning
confidence: 99%
See 2 more Smart Citations